Kegiatan Literasi Sebagai Upaya Pengembangan Kemampuan Berpikir Kritis Pada Siswa - Eka Putri Wulandari; Achmad Muthali'in (Peneliti.net, 2023)
The low literacy rate in Indonesia causes a mindset shift. Students' critical thinking abilities must be honed through literacy-based activities. This study seeks to determine the implementation of literacy activities designed to foster critical thinking in students. This investigation was carried out at Gondangrejo State Senior High School. Utilizing a case study methodology, observation, interviews, and documentation are utilized to conduct qualitative research. Participants in the data collection included school principals, literacy coaches, and students. Triangulation is used to validate the information obtained from sources. This research uses Miles and Huberman's interactive analysis technique to analyze the data. Literacy activities at Gondangrejo State Senior High School were carried out through two methods, a special schedule and classroom instruction. Literacy is held on a special schedule every Friday with three reading resource activities, including free articles, fiction, and poetry. In contrast, literacy instruction includes pre-activity, activity, and post-activity phases. These literacy activities hone students' critical thinking skills, particularly in their responses to reading material outlined in literacy journals.